An Economic Evaluation of rt-PA Locking Solution in Dialysis Catheters - Manns, Braden J. (J Am Soc Nephrol, 2014)
In a recent randomized trial, weekly recombinant tissue plasminogen activator (rt-PA), 1 mg per lumen, once per week, and twice-weekly heparin as a locking solution (rt-PA/heparin) resulted in lower risks of hemodialysis catheter malfunction and catheter-related bacteremia compared with thrice-weekly heparin (heparin alone). We collected detailed costs within this trial to determine how choice of locking solution would affect overall health care costs, including the cost of locking solutions and all other relevant medical costs over the course of the 6-month trial. Nonparametric bootstrap estimates were used to derive 95% confidence intervals (CIs) and mean cost differences between the treatment groups. The cost of the locking solution was higher in patients receiving rt-PA/heparin, but this was partially offset by lower costs for managing complications. Overall, the difference in unadjusted mean cost for managing patients with rt-PA/heparin versus heparin alone was Can$323 (95% CI, −$935 to $1581; P=0.62). When the costs were extrapolated over a 1-year time horizon using decision analysis, assuming ongoing rt-PA effectiveness, the overall costs of the strategies were similar. This finding was sensitive to plausible variation in the frequency and cost of managing patients with catheter-related bacteremia, and whether the benefit of rt-PA on catheter-related bacteremia was maintained in the long term. In summary, we noted no significant difference in the mean overall cost of an rt-PA/heparin strategy as a locking solution for catheters compared with thrice-weekly heparin. Cost savings due to a lower risk of hospitalization for catheter-related bacteremia partially offset the increased cost of rt-PA.